THE EFFECT OF TRANSFER TRAINING AND QUALITY OF WORK LIFE ON NURSING PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS A INTERVENING VARIABLE STUDI OF NURSING AT SULTAN AGUNG ISLAMIC HOSPITAL - Irhamni, Muhammad Ricza; Rahardja, Edy (Universitas Negeri Yogyakarta, 2021)
The purpose of this study is to analyze and explain the effect of training transfer and quality of work life on nurse performance with organizational commitment as an intervening variable (study of nurses in RSI Sultan Agung). The population of this study is all nurses of RSI Sultan Agung, the sampling technique used is simple random sampling, collection data using a questionnaire with criteria of respondents which has married and ever followed in training in last then 7 months. Taken data as many 71 questionnaires, and which can be used as many 68 questionnaires. Data processing and analysis using SEM (structural equation modeling) with PLS (partial least square) technique. The results of this study found that the transfer of training has a significant positive effect on nurse performance; quality of work life has a significant positive effect on nurse performance; transfer training has a significant positive effect on organizational commitment; quality of work life has a significant positive effect on organizational commitment; and organizational commitment has not significant effect on nurse performance. The findings are discussed in the light of previous evidence, and the implications can be used for the company.